The Effects of Cultural Differences on Team Performance in Taiwanese Multinational Enterprises A Case Study of Nova Design - WANG, SZU-HUA (2014)
The purpose of this research is to provide a better understanding of individual’s perspectives on the relationship between cultural diversity and team performance in multinational enterprises. While there has been some research into the effects of cultural variety, few studies have examined the effects of cultural diversity in specific industries. In order to fill to this gap in the literature, this paper will investigate the effects cultural diversity is having on team dynamics in a multinational Taiwanese design firm. Interviews were chosen as a qualitative research methodology, and the study was conducted with three objectives as shown below: 1. To examine how cultural diversity has an impact on team performance, with an especial interest in the relationship of cultural diversity and individualism/collectivism. 2. To investigate the effects cultural diversity has on the cohesiveness of a team, looking specifically at team trust, team communication, team creativity and team conflict. 3. To examine how cultural diversity and leadership styles are related. Findings from the study provide a great deal of evidence of the link between cultural diversity and the effectiveness of teams in a design firm. The paper found both positive and negative outcomes of cultural diversity in a design firm, such as the cultural heterogeneity promoted creativity wile it could also lead to conflict between team members.